Structural Analysis of Subsurface Rock Layers Using Geoelectrical Resistivity Methods Schlumberger Configuration And Dipole Dipole In Ngalan Village - Hasan, Muh. Waqiatul (SAINFIS: Jurnal Sains Fisika, 2022)
Research has been carried out to detect the structure of the rock layers below the surface in the Ngalang village. This research uses resistivity geoelectric method with Schlamberger and Dipole-dipole configurations. Data acquisition using single channel resistivity brand Oyo McOHM Type 2115 A. Measurements were carried out at 1 stretch with a stretch of 300 meters and 1 track with a track 120 meters. Data processing was carried out using Progress and Res2Dinv software with the results in the form of a cross-sectional image of the subsurface resistivity model 1 D and 2D are used to determine the rock layer structure. The measurement results of the schlamberger configuration show that the rock layers with a resistivity value varying from 8.52 Ωm - 409.87 Ωm, while the measurement results of the dipole-dipole configuration show that the rock layers with a resistivity value varying from 15.7 Ωm - 1,713 Ωm. The interpretation results show rock layers with good porosity to bad porosity.